2014
DOI: 10.1371/journal.pone.0096144
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Relationship between Self-Reported Presence and Anxiety in Virtual Reality Exposure Therapy for Anxiety Disorders

Abstract: In virtual reality exposure therapy (VRET) for anxiety disorders, sense of presence in the virtual environment is considered the principal mechanism that enables anxiety to be felt. Existing studies on the relation between sense of presence and level of anxiety, however, have yielded mixed results on the correlation between the two. In this meta-analysis, we reviewed publications on VRET for anxiety that included self-reported presence and anxiety. The comprehensive search of the literature identified 33 publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
107
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 66 publications
9
107
2
9
Order By: Relevance
“…In other words, those participants reporting higher stress levels were also more likely to feel involved and spatially present during the task, regardless of the manner in which the virtual audience was presented. These results concur with those of Ling, Nefs, Morina, Heynderickx, and Brinkman (2014), who found a correlation between sense of presence and anxiety, but not for sex or type of projection of the virtual environment (e.g., field of view, degree of freedom of the tracker, etc.). Since we did not measure anxiety levels in the present study, we cannot say whether a greater spatial presence leads to a higher level of anxiety, but we did find that those participants with higher levels of stress prior to the TSST-VR protocol showed a higher level of involvement and a greater sense of spatial presence, as measured by the IPQ.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, those participants reporting higher stress levels were also more likely to feel involved and spatially present during the task, regardless of the manner in which the virtual audience was presented. These results concur with those of Ling, Nefs, Morina, Heynderickx, and Brinkman (2014), who found a correlation between sense of presence and anxiety, but not for sex or type of projection of the virtual environment (e.g., field of view, degree of freedom of the tracker, etc.). Since we did not measure anxiety levels in the present study, we cannot say whether a greater spatial presence leads to a higher level of anxiety, but we did find that those participants with higher levels of stress prior to the TSST-VR protocol showed a higher level of involvement and a greater sense of spatial presence, as measured by the IPQ.…”
Section: Discussionsupporting
confidence: 90%
“…As already briefly defined above, presence can be described as a user's subjective psychological response to a VR system or the sense of "being there" (Reeves, 1991;Slater, 2003). Researchers agree that presence should trigger the experience of fear and anxiety in virtual environments for phobia treatment and training (Ling et al, 2014). Inducing these emotional states is crucial for clients to confront them and train certain skills to overcome their fear (Wiederhold and Wiederhold, 1998).…”
mentioning
confidence: 99%
“…Inducing these emotional states is crucial for clients to confront them and train certain skills to overcome their fear (Wiederhold and Wiederhold, 1998). However, recent research revealed that the correlation between presence measures and anxiety showed mixed results and differed between phobias (Ling et al, 2014). A recent meta-analysis (Ling et al, 2014) even showed a null-effect for social anxiety [see also Felnhofer et al (2014)].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using 360 o cameras, we can take images and videos of real-life situations and view them in 360 o surround view using a smartphone and low-cost VR headset (costing under $25). These VR tools hold great potential to assess how individuals with mental health problems respond in 'emotionally charged' environments, and to individualize and tailor exposure scenarios to target specific fears, whilst maintaining immersion and presence thought to be key components of VR (Ling et al 2014).…”
mentioning
confidence: 99%